Candidate nomination rules and party leader strategies. (May 2021) - Tromborg, Mathias Wessel
Parliamentary party leaders have an electoral incentive to protect the informational value of their party's label by promoting unity, but recent research has shown that parties can also benefit electorally from appealing broadly through a wide distribution of candidate positions on political issues. This article suggests that party leaders with formal candidate nomination powers balance these incentives by nominating new candidates who are more congruent with the party when the distribution of issue positions among the senior candidates is wide, and, conversely, by nominating new candidates who are more divergent from the party when the senior candidate position distribution is narrow. These possibilities are tested with candidate survey data from six parliamentary democracies, and the results show that new party leader nominations are indeed conditional on the senior candidate distribution, but only on issues that are salient to the party's electoral brand.